Effect of High Ethanol Content Diesel–Ethanol–Biodiesel Blends on Performance and Emissions of a Diesel Engine - Pham, Huu Tuyen; Pham, Minh Tuan; Nguyen, Van Ninh (Old Journal, 2020)
Research on using biodiesel and bioethanol for an internal combustion engine is necessary to solve the shortage of mineral fuels and environmental pollution. This paper presents the results of simulating the engine performance and emissions of a Hyundai D4BB 4-cylinder diesel engine when using high ethanol content diesel–ethanol–biodiesel blends. The model of engine fueled by fossil diesel was calibrated and validated by experiment which was carried out on engine test benches. The result shows that, when using blends including DE10B5 (85% diesel–10% ethanol–5% biodiesel), DE30B5 (65% diesel–30% ethanol–5% biodiesel), DE50B5 (45% diesel–50% ethanol–5% biodiesel), engine power decreases and fuel consumption increases at full load whereas the concentration of CO, NOx, soot emissions decreases at all operation loads as compared to that when using fossil diesel.